Culture negative orthopedic biofilm infections - Ehrlich, Garth D. (Springer series on biofilms, 2012)
This book describes orthopedic biofilm infections, reviewing current strategies based on the meticulous removal of compromised tissues, antibiotic options based on high biofilm-killing local doses, and practical bedside strategies for dealing with infection